Penerapan Metode Analytical Hierarchy Process Dan Technique for Order Preference by Similarity to Ideal Solution Sebagai Pendukung Keputusan Dalam Menentukan Kenaikan Jabatan Bagi Guru - Sri Siswanti; Fatwa Lingga Wrehatnala; Andriani Kusumaningrum (Jurnal Ilmiah SINUS, 2020)
Thesis report entitled “Application of AHP and TOPSIS Method as Decision Support System in Determining Position Promotion for Teachers of Vocational High School in Surakarta” is based on research by the author carried out located in Jl. Dr. Wahidin 33 Surakarta on 28 September 2018 – 6 Agustus 2019. The purpose of this paper is to make Application of AHP and TOPSIS Method as Decision Support System in Determining Position Promotion for Teachers of Vocational High School in Surakarta to integrate the selection of recipients in order to avoid manipulation of the data in the provision of accurate decisions. Data collection was conducted by the author uses descriptive method that includes field studies and literature. Field studies were conducted are interviews with the Vocational High School related problems. While the literature study is useful to get a theoretical basis in the form of expert opinion on matters which is the object of research. It is also used to assist writers in the execution of a research report by the author. The result of the manufacturing Application of AHP and TOPSIS Method as Decision Support System in Determining Position Promotion for Teachers of Vocational High School Surakarta consists of input data including teachers data, criteria data, the data classifications, and data input analysis. The results of position promotions for teachers on Vocational High School Surakarta was given to best alternative with score of 88.12, while on using with AHP and TOPSIS method was given to best alternative with score of 0.7238.